Habit as Love in Christian Theology (The Heretic (Ceased Publication 2023), 2023)
Have you ever tried to learn to play an instrument, to frame out a wall, or to run a mile without stopping? If you have, you know this: there is no way to build a skill without practice, practice which forms habit. And have you ever tried to squash a propensity for nail-biting, nose-picking, or some comparable vice? If you have, you know this: habit, once established, is as if carved in stone.